General Clauses and the Abuse of Subjective Right in the Polish Labor Code - Baran, Krzysztof (PRAWO i WIĘŹ, 2023)
The article is devoted to general clauses regulating abuse of law in the Polish Labor Code. The author defined the meaning of the concept of a general clause and its functions. He also discussed the legal mechanism of the functioning of the socioeconomic abuse of law category and principles of social coexistence in individual and collective labor law.